FOXM1/lncRNA TYMSOS/miR-214-3p–Mediated High Expression of NCAPG Correlates With Poor Prognosis and Cell Proliferation in Non–Small Cell Lung Carcinoma - Yuan, Yixiao; Jiang, Xiulin; Tang, Lin; Wang, Juan; Zhang, Dahang; Cho, William C.; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Abstract Lung cancer is the most common tumor with severe morbidity and high mortality. Increasing evidence has demonstrated that non-SMC condensin I complex subunit G (NCAPG) play crucial role in the progression of human cancer. However, the functions and mechanism of NCAPG in NSCLC are still barely known. Here, we utilized the diverse public databases analysis the expression of NCAPG in human varies cancer, the results shown that NCAPG was highly expression in diverse human cancer, especially in lung cancer. NCAPG level was significantly positive correlated with poor clinic-pathologic features, poor prognosis, TMB, MSI and immune cell infiltration in lung cancer. In addition, our results demonstrate that depletion of NCAPG significantly inhibits NSCLC cell proliferation, migration and self-renewal abilities, which could be reversed by miRNA-214-3p. Finally, we identified the upstream regulatory mechanism of NCAPG, namely FOXM1/THYMSOS/ miRNA-214-3p axis. Knock down of THYMSOS also inhibits the NSCLC cell proliferation, migration and self-renewal abilities. Collectively, our findings demonstrated the oncogenic roles of the FOXM1/lncRNA-TYMSOS/miRNA-214-3p /NCAPG axis in NSCLC, represent NCAPG have the potential of as an effective therapeutic target in future.